Comprehensive Analysis Reveals PTK6 as a Prognostic Biomarker Involved in the Immunosuppressive Microenvironment in Breast Cancer - Lili Wang; Shuimei Luo; Ziming Wang; Yiqiang Huang; Yang Luo; Xianhe Xie (Journal of Immunology Research)
The significant mortality rate that is currently experienced by female breast cancer (BC) patients highlights the importance of locating potent and dependable biomarkers in BC patients. Over the past few years, a number of studies have demonstrated that PTK6 was dysregulated in a variety of cancers. However, its expression and the clinical importance it may have in patients with BC have not been explored. Based on datasets from the TCGA database and GTEx database, we studied the expressions and functions of PTK6 across 33 different kinds of cancer. In this study, we investigated the differential expression of PTK6 in tumor tissue compared to nontumor tissue as well as in various stages of cancer. ROC assays were used to conduct an investigation into the diagnostic potential of PTK6 in BC. After that, the Kaplan-Meier method, univariate analysis, and multivariate analysis were carried out in order to investigate the PTK6 gene’s potential prognostic significance in patients with BC. ssGSEA was utilized in order to conduct an investigation of the immune infiltration. In this study, we discovered that the expressions of PTK6 were significantly raised in the majority of different types of malignancies, including BC. The diagnostic value of PTK6 expression was validated by ROC tests, demonstrating an AUC greater than 0.7. A positive PR, ER, and HER2 status was found to be related with high expression levels of PTK6. According to the results of a survival analysis, patients who had a high level of PTK6 expression had a shorter overall survival time than those who had a low level of PTK6 expression. Besides, we observed that PTK6 expressions were positively correlated with the abundance of NK CD56bright cells and Th17 cells and negatively correlated with that of Th1 cells, macrophages, B cells, T cells, aDC, DC, cytotoxic cells, Tem, TFH, NK CD56dim cells, Treg, and Tgd. In conclusion, PTK6 expression was found to be linked with the clinical phenotype of BC, and as a result, this finding may have consequences for the diagnosis, prognosis, and treatment of individuals with BC.